Refractory Central Neurogenic Hyperventilation: A Novel Approach Utilizing Mechanical Dead Space - Sweidan, Alexander J.; Bower, Matthew M.; Paullus, Jeffrey; Sterpi, Michelle; Stern-Nezer, Sara; Dastur, Cyrus; Yu, Wengui; Groysman, Leonid I. (Frontiers in Neurology, 2019)
This report describes the successful management of a case of central neurogenic hyperventilation (CNH) refractory to high dose sedation by increasing mechanical dead space. A 46-year-old male presented with a history of multiple neurological symptoms. Following an extensive evaluation, he was diagnosed with primary diffuse CNS lymphoma and started on high dose steroids. After an initial symptomatic improvement, the patient developed increasing respiratory distress and tachypnea. He was intubated and transferred to the neurointensive care unit (neuro ICU). While in the ICU the patient continued to be ventilator dependent with significant tachypnea and respiratory alkalosis resistant to fentanyl and propofol. This prompted an attempt to normalize the PaCO2 via an increase of the mechanical dead space. This approach successfully increased PaCO2 and bridged the patient until ongoing therapy for the underlying disease resolved the pervasive breathing pattern typical of CNH. Further investigation is warranted to evaluate this strategy, which upon review of the literature appears underused.